2016
DOI: 10.18632/oncotarget.12220
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs LOC285194, RP11-462C24.1 and Nbla12061 in serum provide a new approach for distinguishing patients with colorectal cancer from healthy controls

Abstract: Colorectal cancer (CRC) is currently the most prevalent malignant cancer worldwide. However, there is a lack of efficient biomarkers for CRC screening. Accumulating evidence reveals that long non-coding RNAs (lncRNAs) detectable in serum are associated with the genesis and development of various types of cancer. Therefore, we examined the diagnostic ability of lncRNAs in blood samples from patients with CRC by evaluating the levels of 17 CRC- or gastrointestinal cancer-related lncRNAs in serum samples from 71 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…At the same time, we detected the cell supernatant and found several detectable lncRNAs. There were also many reports indicating that lncRNAs were detectable in the blood [ 31 , 32 ]. Therefore, we performed screening in the serum of HCC patients, non-cancer patients and healthy individuals to comprehensively and systematically explore the function and value of lncRNAs in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we detected the cell supernatant and found several detectable lncRNAs. There were also many reports indicating that lncRNAs were detectable in the blood [ 31 , 32 ]. Therefore, we performed screening in the serum of HCC patients, non-cancer patients and healthy individuals to comprehensively and systematically explore the function and value of lncRNAs in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The technique for detection and measurement of specific serum lncRNAs has become feasible, which provides a new method without invasiveness for the identification of new biomarker for cancer. Recent studies found that serum lncRNAs are useful for the diagnosis of multiple types of cancer, such as bladder cancer [ 69 ], liver cancer [ 70 ], cervical cancer [ 71 ], gastric cancer [ 72 ], colorectal cancer [ 73 , 74 ] and breast cancer [ 75 ] etc, these serum lncRNAs may even serve as prognostic biomarkers [ 69 , 72 , 74 ]. Serum lncRNAs in RCC patients are also deregulated.…”
Section: Lncrnas In Rccmentioning
confidence: 99%
“…17 Second, in serum samples, for example, LOC285194 and RP11-462C24.1 can provide a new method that could differentiate patients with CRC from healthy controls. 67 Furthermore, several dysregulated lncRNAs are present in both cancer tissues and patient serum samples, such as BANCR, NR_034119, NR_029373, and NR_026817. 79 In conclusion, lncRNA is involved in the development and progression of CRC and shows that lncRNA may be a potential diagnostic and new prognostic target in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%